2011
DOI: 10.1097/coc.0b013e3181e841ce
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Trimodality Therapy for Esophageal Cancer

Abstract: Patients with microscopic residual disease following trimodality therapy had similar outcomes to patients achieving a pCR. Patients with SCC were more likely to achieve a pCR, and had a higher propensity to fail distantly when compared with patients with AC. This data should be considered in the design of future clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…18 Our 2-year PAF rate was higher at 9%, which was likely related to the finding that a greater percentage of patients in the current study had adenocarcinoma (79% vs 68%), with the majority involving the GEJ. We found the highest rates of PAF (19%) among patients with adenocarcinoma of the GEJ who had ≥2 clinically involved lymph nodes at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 49%
“…18 Our 2-year PAF rate was higher at 9%, which was likely related to the finding that a greater percentage of patients in the current study had adenocarcinoma (79% vs 68%), with the majority involving the GEJ. We found the highest rates of PAF (19%) among patients with adenocarcinoma of the GEJ who had ≥2 clinically involved lymph nodes at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 49%
“…All PET/CT studies were acquired on the same scanner following an institutional standard protocol (10). All patients were treated with external-beam radiotherapy to the same total dose of 50.4 Gy with concurrent Cisplatin or Carboplatin chemotherapy (14). …”
Section: Methodsmentioning
confidence: 99%
“…With a median interval of time from completion of radiation to surgery of 49 days, they reported no difference in patient outcomes based on the interval from radiation completion and surgery. Similarly, Koshy et al, found that with a median time lapse of 7 weeks between treatments, there was no significant effect on tumor response (20). …”
Section: Commentmentioning
confidence: 98%